Midwives' account of virtual reality childbirth education - Marjaana Siivola; Lauri Malmi (Finnish Social and Health Informatics Association, 2024)
In Finland, prenatal clinics and birthing hospitals struggle with resources to provide expectant parents with childbirth education (CBE) and a tour of the hospital birthing unit. Not preparing for birth is common, and not knowing how and where to give birth causes parents unnecessary stress during pregnancy. One new possibility to complement CBE is using virtual reality (VR) to deliver content. The aim of this study is to describe midwives' views of the status of parents' preparation for birth and provide information on the VR CBE program's advantages and challenges from the midwife's perspective. The study consisted of two focus group sessions with seven participants. Participants were midwives with experience from a hospital birthing ward and had provided childbirth education. The data was analysed using a thematic content analysis approach. According to the midwives, the parents do not prepare for birth well enough. Preparing for birth affects the parents' knowledge about childbirth, their cooperation with the healthcare personnel, and how they trust the birthing process, themselves, and the healthcare personnel. Preparation can also have adverse effects if the birthing person is trying to give birth with a detailed plan or has false expectations. Parents should focus on knowledge, attitude, and mental and physical exercise in preparing for childbirth. By preparing from trusted sources, parents can make informed decisions. They have the skills to stay calm, relaxed, and open-minded during labour and birth. Physical and mental exercise will help them cope with labour and relax their mind and bodies during birth. Midwives see VR as offering great potential for concrete, realistic, and flexible childbirth education that can address current challenges. They were also worried that VR could replace face-to-face contact. However, since there is minimal such contact in the current CBE, VR could enhance childbirth education and offer a realistic and concrete image of birth and a hospital tour. Midwives want families to prepare better for birth and work on their knowledge, attitude, and exercise. By preparing, parents understand childbirth, trust themselves, the birthing process, and the midwives; cooperation works better. Midwives see VR as an excellent addition to childbirth education by offering realistic and concrete online childbirth education. VR should not replace face-to-face contact.